2007
DOI: 10.1128/aem.01543-07
|View full text |Cite
|
Sign up to set email alerts
|

Low Densities of Epiphytic Bacteria from the Marine Alga Ulva australis Inhibit Settlement of Fouling Organisms

Abstract: Bacteria that produce inhibitory compounds on the surface of marine algae are thought to contribute to the defense of the host plant against colonization of fouling organisms. However, the number of bacterial cells necessary to defend against fouling on the plant surface is not known. Pseudoalteromonas tunicata and Phaeobacter sp. strain 2.10 (formerly Roseobacter gallaeciensis) are marine bacteria often found in association with the alga Ulva australis and produce a range of extracellular inhibitory compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 69 publications
1
114
0
Order By: Relevance
“…For instance, Pseudoalteromonas tunicata and Phaeobacter sp. strain 2.10 (formerly Roseobacter gallaeciensis) isolated from the alga U. australis inhibited larval settlement of the bryozoan Bugula neritina at densities of 10 3 to 10 5 cells cm À2 , which are similar to the densities of these bacteria under natural conditions (Rao et al 2007). Multispecies biofilms with similar composition to those from the alga Fucus vesiculosus inhibited the settlement of cyprid larvae of the barnacle Amphibalanus improvisus (Nasrolahi et al 2012).…”
Section: Antilarval Activity Heterotrophic Bacteriamentioning
confidence: 58%
See 1 more Smart Citation
“…For instance, Pseudoalteromonas tunicata and Phaeobacter sp. strain 2.10 (formerly Roseobacter gallaeciensis) isolated from the alga U. australis inhibited larval settlement of the bryozoan Bugula neritina at densities of 10 3 to 10 5 cells cm À2 , which are similar to the densities of these bacteria under natural conditions (Rao et al 2007). Multispecies biofilms with similar composition to those from the alga Fucus vesiculosus inhibited the settlement of cyprid larvae of the barnacle Amphibalanus improvisus (Nasrolahi et al 2012).…”
Section: Antilarval Activity Heterotrophic Bacteriamentioning
confidence: 58%
“…Bacteria associated with the green alga Ulva lactuca have been shown to have antibacterial and antialgal activity (Table 4; Rao et al 2007;Kumar et al 2011). Eighty percent of epibiotic isolates from U. lactuca inhibited growth of the diatom Cylindrotheca fusiformis .…”
Section: Antialgal Activity Heterotrophic Bacteriamentioning
confidence: 99%
“…Despite this genomic evidence for a surfaceattached lifestyle (Supplementary Material S13), colonization of P. gallaeciensis has only been investigated for one natural surface type, the green alga U. lactuca (Rao et al, 2007). Therefore, green fluorescent protein (GFP)-labeled cells of P. gallaeciensis DSM 17395 were added to a variety of micro-and macroalgae, crustacean tissue and driftwood.…”
Section: Attachment To and Interaction With Surfacesmentioning
confidence: 99%
“…Because of the competitive success of Phaeobacter spp. against fish and mollusc pathogens, ongoing research focuses on these organisms as probiotic agents in aquaculture (Rao et al, 2007;Porsby et al, 2008;Prado et al, 2009). Most recently, it was shown that P. gallaeciensis also produces algicides upon sensing the lignin-derived breakdown product p-coumaric acid from a co-cultivated microalga (Seyedsayamdost et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other reports indicated that epiphytic bacteria, which produce bioactive substances, enhanced the fitness of their algal host (Rao et al 2007). We suggest that the metabolites DAPG, MAPG, PLT and rhizoxins act against competitors and degrading or other deleterious microorganisms, like fungal and bacterial pathogens of Saccharina latissima.…”
Section: Bioactivity Of Metabolites Produced Bymentioning
confidence: 92%